Health education in schools: knowledge of adolescents about the Human Immunodeficiency Virus (Research, Society and Development, 2021)
Objective: to learn the knowledge of adolescents about the Human Immunodeficiency Virus and describe health education actions in schools. Methodology: a descriptive-exploratory study with a mixed approach developed with theoretical support from action research, in two public schools, located in the city of Recife, Pernambuco, Brazil. 188 students from elementary school II and high school participated. Data were collected through a questionnaire with open and closed questions. For data analysis, descriptive statistics and categorical content analysis were performed. Results: the contents were organized into two categories: knowledge about transmission and knowledge about prevention. It was apprehended that students recognize unprotected sexual activity as the main form of transmission of the virus. But they do not carry out preventive practices about which they have superficial knowledge. Among the educational actions in schools, the reflection on the combined prevention strategy for the transformation of realities, the construction of new knowledge and the consolidation of previous knowledge stood out. Conclusion: it is considered necessary to insert in the school context, in a permanent and participatory manner, health promotion and education aimed at the transformation and emancipation of knowledge about the virus.